2005
DOI: 10.2165/00007256-200535020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Conditioning on Children and Adolescents with Asthma

Abstract: More than 40 years ago, the effects of exertional dyspnoea and the associated fear of an asthma attack usually lead to an avoidance of physical activity amongst asthmatic children. This issue still exists today, particularly in children with severe asthma. This article presents a comprehensive review of published information concerning the effects of training programmes on children and adolescents with asthma. The primary focus of these investigations was to examine the effects of physical conditioning on aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1
18

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 36 publications
3
93
1
18
Order By: Relevance
“…29 This was demonstrated in a study by Thickett et al 33 and warranted an editorial on the matter. 34 The pool facility in which our patients trained did not have our sample experienced asthma attacks during swimming or in the first few hours after swimming.…”
Section: Allergy Skin Testingmentioning
confidence: 90%
See 1 more Smart Citation
“…29 This was demonstrated in a study by Thickett et al 33 and warranted an editorial on the matter. 34 The pool facility in which our patients trained did not have our sample experienced asthma attacks during swimming or in the first few hours after swimming.…”
Section: Allergy Skin Testingmentioning
confidence: 90%
“…This fact was addressed at length in a Thorax editorial 25 While some studies have shown beneficial effects of swimming on pulmonary function test parameters, 11,15 others have failed to show any such effect. 3,10,13,29 However, none of these studies used BHR assessment as a followup tool. BHR must be assessed, especially in studies that evaluate response to asthma treatment over time.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
“…2 But research shows that parental knowledge is often poor and misperceptions common 17,28 and, therefore, [29][30][31] Experimental research shows that young people with asthma frequently misinterpret breathlessness as asthma, when it is actually due to low aerobic fitness stemming from avoiding exercise. 6 For the vast majority of children, exercise tolerance has been shown to be limited by muscular factors and not the lungs. 32 Even at exercise exhaustion, pulmonary reserve is considerable.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…5 However, it has specific benefits for children with asthma, including reduced hospital admissions, reduced school absenteeism, fewer consultations with GPs, reduced medication, 6 and improved ability to cope with asthma. 7 Despite these benefits, rates of physical activity among young people with asthma are lower than their nonasthmatic peers, [8][9][10][11][12] and are continuing to decline as rates fall more generally among young people in most industrialised nations.…”
Section: Introductionmentioning
confidence: 99%
“…A realização de exercícios físicos regulares usados como complemento dos tratamentos de crianças asmáticas, sugere evidências também de redução da falta de ar (Ram et al, 2000) e do broncoespasmo induzido por exercício . Baseado nestes achados, pacientes asmáticos têm sido encorajados a participar em programas regulares de exercícios físicos (Welsh et al, 2005). Na literatura, não há consenso de qual o melhor exercício para a criança asmática e diversas atividades têm sido propostas tais como corrida, exercícios calistênicos, futebol, vôlei, ciclismo, natação e alongamento, entre outras (Ram et al, 2000).…”
Section: Introductionunclassified